2018
DOI: 10.31092/jia.v2i1.237
|View full text |Cite
|
Sign up to set email alerts
|

Pengeluaran Pemerintah Dan Perkembangan Perekonomian (Hukum Wagner) Di Negara Sedang Berkembang: Tinjauan Sistematis

Abstract: Hubungan kausal antara pengeluaran pemerintah dengan perkembangan perekonomian dapat dikaji lewat dua pandangan, yaitu Hukum Wagner atau Hipotesis Keynes. Hukum Wagner memandang bahwa pengeluaran pemerintah merupakan dampak dari perkembangan ekonomi, sedangkan Hipotesis Keynes berpendapat bahwa pengeluaran pemerintah merupakan alat kebijakan fiskal untuk meningkatkan perekonomian. Dua pandangan tersebut secara akademis masih diperdebatkan, terbukti dengan banyak artikel ilmiah yang membahasnya. Sayangnya, simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
1
12
0
4
Order By: Relevance
“…It encourages society should increase demand through spending. The conclusion from this theory is that government spending has an effect on economic development (Solikin, 2018). The concept of national income with the government expenditure approach is formulated by Y = C + I + G + X -M (Anitasari & Soleh, 2015).…”
Section: Figure2 Proportion Of Central Government Expenditure In 2019mentioning
confidence: 99%
See 1 more Smart Citation
“…It encourages society should increase demand through spending. The conclusion from this theory is that government spending has an effect on economic development (Solikin, 2018). The concept of national income with the government expenditure approach is formulated by Y = C + I + G + X -M (Anitasari & Soleh, 2015).…”
Section: Figure2 Proportion Of Central Government Expenditure In 2019mentioning
confidence: 99%
“…The last hypothesis is that there is a good two-way causality between GDP and government spending. Several previous researchers compared Wagner's Law with Keynes's Theory because the two opinions contradict each other (Solikin, 2018). Testing Wagner's Law is not our focus, because various studies conducted by previous researchers have concluded that Wagner's Law usually applies to developed countries, which means that the more developed an economy is, the more government spending is affected.…”
Section: Wagner's Lawmentioning
confidence: 99%
“…The theory states that government spending and government activities will increase over time. This tendency by Wagner is called the law of always increasing role of government (Clark, 1940;Solikin, 2018). Meanwhile, Rostow and Musgrave in their model connects the development of government spending with the stages of economic development which are separated for each stage, namely at the initial stage, the intermediate stage and the advanced stage.…”
Section: (3)mentioning
confidence: 99%
“…Dalam studi keuangan publik, terdapat pendapat yang menyatakan bahwa pendapatan pajak akan memengaruhi belanja, pengeluaran belanja akan meningkatkan penerimaan pajak, atau hubungan timbal balik dua arah antara pendapatan dan belanja (Sriyana, 2012). Hasil review atas penelitian empiris menunjukkan bahwa ketiga jenis hubungan tersebut dilaporkan dalam penelitian di negara sedang berkembang (Solikin, 2018). Dikaitkan dengan belanja, pada umumnya pemerintah menganut pandangan Keynesian daripada pandangan Wagner, yaitu peran pemerintah sangat penting dalam perekonomian dengan menggunakan belanja (APBN) untuk menggerakkan perekonomian, setidaknya dalam jangka pendek.…”
Section: Peran Belanja Pemerintahunclassified